Organ Body Weight Relationship of Some Organs in the Male African Grasscutter (Thryonomys swinderianus) - Ajayi, Itopa Etudaye; Shawulu, James Clinton; Nafarnda, Wesley Daniel (Journal of Advanced Veterinary Research, 2012)
Studies were conducted to examine the relationship between the organ-body weights. Six apparently healthy adult grasscutters were used for the study. Organ weights considered were the liver, lungs, kidneys, spleen and testes, all of which were recorded as mean Â± SEM. A highly positive correlation existed between the right testis and the body weight (r = 0.950, p < 0.05). The left testis and the body weight also exhibited high positive relationship (r = 0.904, p < 0.05). Bilateral asymmetry of paired organs was observed, very high positive relationships existed between the right and left lungs (r = 1.000, p < 0.05), the right and left kidneys (r = 0.968, p < 0.05) and also the right and left testes (r = 0.985, p < 0.05). For cases of significant relationships, we infer that the variables or their combinations could provide a good estimate for predicting live weights of the African grasscutter.